The Exploratorium Science Snackbook: Cook Up Over 100 Hands-On Science Exhibits from Everyday Materials - Bartels Dennis (Jossey-Bass, 2009)
Kids and teachers can build their own science projects based on exhibits from San Francisco's premiere science museum